Komunikasi Sinergistik Pemerintah Kota Banda Aceh Dan Majelis Pengajian Tauhid Tasauf Dalam Mewujudkan Masyarakat Seimbang - Syukri Syamaun (Jurnal Peurawi: Media Kajian Komunikasi Islam, 2019)
This article discusses the role of Banda Aceh Govermen and islamic teachings on tasauf in creating social, cultural, and contextual forces as factors affecting synergetic communication for living together, which further give contributes to protecting society againt radicalism. This article argues that the cooperating between Banda Aceh Goverment and Islamic teachings on tasauf can be an alternative power introducing peace without spreading hates each other. The teaching itself led and followed by ulama and people from any different place and thought of Islam. They always able to work together in creating individual and social forces by their abilities of social communication skills.